2016
DOI: 10.3928/01477447-20151218-12
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor Caused by Titanium Particles From a Total Hip Prosthesis

Abstract: A 77-year-old woman underwent metal-on-polyethylene total hip arthroplasty for osteoarthritis of the right hip at another institution. During surgery, the greater trochanter was broken and internal fixation was performed with a trochanteric cable grip reattachment. Although postoperative recovery was uneventful, approximately 6 years later, the patient had severe right hip pain with apparent swelling, and she was referred to the authors' institution. Plain radiographs showed evidence of severe osteolysis in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…They concluded that a chronic host inflammatory response and a delayed foreign-body hypersensitivity response were both integral to titanium pseudotumor formation. Despite being unable to perform atomic spectrometry for our samples, intraoperative pathology obtained from our patient's pseudotumor was consistent with that of Sakamoto et al, who reported the presence of many inflammatory cells (CD3-, CD4-, and CD8-positive lymphocytes; plasma cells; and histiocytes) and metal debris [23].…”
Section: Discussionsupporting
confidence: 84%
“…They concluded that a chronic host inflammatory response and a delayed foreign-body hypersensitivity response were both integral to titanium pseudotumor formation. Despite being unable to perform atomic spectrometry for our samples, intraoperative pathology obtained from our patient's pseudotumor was consistent with that of Sakamoto et al, who reported the presence of many inflammatory cells (CD3-, CD4-, and CD8-positive lymphocytes; plasma cells; and histiocytes) and metal debris [23].…”
Section: Discussionsupporting
confidence: 84%
“…Soluble and particulate titanium disturbs the delicate balance between the two cell types, resulting in bone loss and implant loosening, which often necessitates a redo surgery (revision surgery) [35,41,56,[59][60][61]. Formation of large inflammatory masses (pseudotumours) in the vicinity of the implant, originally thought to be an immune response unique to CoCr alloy, was recently linked to titanium release [62][63][64]. The pathogenesis of pseudotumor formation is unknown, but it is thought to involve both a chronic inflammatory response and a delayed hypersensitivity response to ultrafine titanium particles [62].…”
Section: Adverse Effects Of Titanium Debrismentioning
confidence: 99%
“…Formation of large inflammatory masses (pseudotumours) in the vicinity of the implant, originally thought to be an immune response unique to CoCr alloy, was recently linked to titanium release [62][63][64]. The pathogenesis of pseudotumor formation is unknown, but it is thought to involve both a chronic inflammatory response and a delayed hypersensitivity response to ultrafine titanium particles [62]. It follows that individuals with a pre-existing titanium sensitivity might be at a greater risk of this particular complication [64].…”
Section: Adverse Effects Of Titanium Debrismentioning
confidence: 99%
“…This oxide layer, while offering corrosion resistance, is quite thin and offers little protection in potential for the release of titanium wear particles into the adjacent tissue ( Li et al., 2010 ). Wear particles pose a serious problem for orthopedic implant success, and several rejected arthroplasties recovered have found wear particles in the surrounding tissue ( Grosse et al., 2015 ; de Pasquale et al., 2018 ; Hall et al., 2019 ; Sakamoto et al., 2016 ). Furthermore, titanium debris has been found to distribute throughout the body, with traces found in the liver, spleen, and lymphatic system ( Urban et al., 2000 ).…”
Section: Titanium As An Orthopedic Biomaterialsmentioning
confidence: 99%